Pemanfaatan Limbah Hidrogel Popok Bayi Sebagai Bahan Campuran Pembuatan Bata Ringan - Nuralfiliani, Nuralfiliani; Mustakim, Mustakim; Jabir, Muhammad (Sultra Civil Engineering Journal (SCiEJ), 2024)
Baby diapers are made of plastic and a mixture of chemicals, a solution to use diaper waste by utilizing hydrogel and plastic contained in diapers. The plastic contained in diapers can be utilized as a lightweight construction material in the form of lightweight bricks to increase compressive strength. This study aims to determine the effect of a mixture of baby diaper waste on water absorption and compressive strength in making lightweight bricks. This research method is experimental, which is carried out at the Structure and Materials Laboratory of the Muhammadiyah University of Parepare. The results showed that each variation with dimensions of 5cm x 5cm with a curing age of 28 days, a variation of 0% with an average compressive strength of 4,000 MPa, a variation of 7% with an average compressive strength of 5,333 MPa, a variation of 12% with an average compressive strength of 9,333 MPa and a variation of 17% with an average compressive strength of 13,333 MPa. Meanwhile, the percentage of water absorption of lightweight bricks with a variation of 0% was 21.2%, a variation of 7% was 23.6%, a variation of 12% was 27.4% and a variation of 17% was 30.1%